Heart transplants in interferon-gamma, interleukin 4, and interleukin 10 knockout mice. Recipient environment alters graft rejection. - Räisänen-Sokolowski, A (1997)
To study the role of cytokines in long-term cardiac allografts we have used recipient mice with targeted gene deletions (-/-) in IFN-gamma, IL-4, or IL-10. In wild-type and IL-4 -/- recipients immunosuppressed with a 30-d course of anti-CD4 and anti-CD8, graft survival was > 87 d. This time was significantly reduced in IFN-gamma -/- (62 +/- 19 d, P < 0.05) and IL-10 -/- recipients (55 +/- 4 d, P < 0.0001). Histology showed mononuclear cell infiltration, patchy necrosis, fibrosis, and vascular thickening in all groups. Intragraft transcript levels measured by 32P-reverse transcriptase PCR showed different inflammatory patterns. IFN-gamma -/- recipients had higher IL-2 transcripts and selective alteration in macrophage activation that may have contributed to decreased graft survival. Decreased graft survival in IL-10 -/- recipients was associated with increases in iNOS and IFN-gamma-driven responses. Finally, in grafts from IL-4 -/- recipients, there were increases in CD3 transcripts concurrent with TNF-alpha levels. This increase suggests that IL-4 may regulate T cell infiltration through TNF-alpha-mediated inflammatory cell recruitment. Concurrent evaluation of these three isolated cytokine deletions has shown that the recipient environment caused distinct graft modifications.